1995
DOI: 10.3171/jns.1995.82.5.0780
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of loculated hydrocephalus

Abstract: Loculated hydrocephalus remains a difficult neurosurgical problem and endoscopes designed to navigate through the ventricular system provide a new option for treatment. The authors review their experience, during the period March 1990 to June 1993, using a steerable fiberscope in 34 cases of loculated hydrocephalus to evaluate the efficacy of endoscopic cyst fenestration. The goals of treatment were to control hydrocephalus, simplify preexisting shunt systems, and reduce operative morbidity. Endoscopic cyst fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 20 publications
1
81
0
1
Order By: Relevance
“…18,[30][31][32][33][34][35][36] This was apparent in our patient before intraventricular tobramycin was instituted because the highest CSF concentration was only 1.3 µg/mL despite a concurrent therapeutic peak serum concentration of 7.1 µg/mL. Our patient experienced variable CSF trough tobramycin concentrations, which ranged from 6.5 to 30.5 µg/mL on 5 mg/day intraventriculary.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…18,[30][31][32][33][34][35][36] This was apparent in our patient before intraventricular tobramycin was instituted because the highest CSF concentration was only 1.3 µg/mL despite a concurrent therapeutic peak serum concentration of 7.1 µg/mL. Our patient experienced variable CSF trough tobramycin concentrations, which ranged from 6.5 to 30.5 µg/mL on 5 mg/day intraventriculary.…”
Section: Discussionmentioning
confidence: 95%
“…[33][34][35][36][37][38][39][40] The potential exists for neuronal tissue irritation and necrosis with high CSF drug concentrations. Our patient had four seizure episodes, one shortly before abscess drainage and daily thereafter for 3 more days.…”
Section: Discussionmentioning
confidence: 99%
“…Success of endoscopic fenestration in the setting of middle fossa arachnoid cysts is well-documented [91,98,99]. In work by Spacca et al, 90 % of the pediatric cohort treated demonstrated clinical improvement, and 73 % of cysts treated reduced in size or completely resolved following intervention [79].…”
Section: Arachnoid Cystsmentioning
confidence: 99%
“…The neuroendoscope has now become established as a means of performing minimally invasive neurosurgery, with particular indications in the treatment of hydrocephalus, biopsy of intraventricular lesions, and penetration of cystic lesions. 13,14,17,18) Applying a navigation system to a rigid endoscope allows real-time navigation of the rigid endoscope tip, and improves the understanding of anatomical structures observed through the endoscope, leading to improved treatment outcomes and safety. Flexible endoscopes can be used in areas difficult to approach by rigid endoscopes, to biopsy tumor lesions, observe the sylvian aqueduct, and evacuate intraventricular and intraparenchymal hematomas.…”
Section: Introductionmentioning
confidence: 99%